INVESTIGATING LINGUISTIC INGENUITY IN RAFAT’S SELECTED POEMS: A STYLISTIC ANALYSIS - Muhammad Haroon Jakhrani; Maleeha Nazim; Muhammad Hassan Shaikh (International Journal of Contemporary Issues in Social Sciences, 2024)
This study’s primary goal is to investigate the inventiveness and creativity of the language used in a few of Rafat’s poems. This study employs a stylistic methodology to achieve its goals. This study has an analytical, qualitative, and theoretical bent. The analysis uses Leech and Short’s (1981) stylistic model. Selected texts were used as a sample of the study. Children understand him, the medal and when we kiss. According to the findings of this study, Rafat used generally comparable stylistic components that, despite certain similarities in the basis of the poems, contributed to deviations and innovations in a few verses while expressing unique and varied meanings in each of his poems. According to the inquiry, several of Rafat’s poems stand out for their ability to reveal intentions and uphold aesthetic worth, proving a lasting influence on literature. Any literary or non-literary text’s language qualities can be discovered using stylistics. As a result, it is anticipated that this research will significantly influence future scholars interested in analyzing poetry, particularly from a linguistic perspective.